A qualitative comparative analysis (QCA) of satisfaction toward extreme sporting Events. Issue 4 (November 2018) - Scarpi, Daniele; Pizzi, Gabriele; Raggiotto, Francesco; Mason, Michela
Highlights: We use QCA to study recipes for satisfaction toward extreme sporting events. We relate psychological drivers of edgework individuals with marketing outcomes. We explore mixed configurations of psychology- and marketing- related variables. Multiple mixed recipes exist for satisfaction toward extreme sporting events. Graphical Abstract: Abstract: We examine participant satisfaction in the context of extreme sporting events, where participants seek intense sensations but want to feel in control over the risky challenges. We combine two streams of literature scarcely related by previous studies, addressing both event-related and psychological attributes of extreme individuals. Because of the complex set of inter-relationships in which the investigated phenomena unfold, complexity theory tenets can provide a more accurate understanding of what generates extreme sport participants' satisfaction toward a sporting event. Applying this perspective, the present research determines the possible combinations that build strong participant satisfaction in the context of extreme sporting events. Through qualitative comparative analysis (QCA), we identify more possible "recipes" that contribute to high levels of satisfaction. Results suggest that attributes related to the event (trust, image, attitude) and attributes related to the psychology of extreme sport participants (sensation-seeking, perceived control) contribute jointly in all "recipes". Furthermore, satisfaction can emerge for events despite low attitude if their image is strong and participants feel in control of the challenges. Chinese Abstract: 我们在极限运动赛事的背景下检查参与者的满意度, 此时参与者寻求强烈的感受, 但希望能够控制有风险的挑战. 我们结合了以前研究中几乎毫不相关的两种文献, 研究了极限运动个体的赛事相关属性和心理属性. 由于所研究现象展开时呈现的复杂相互关系, 对于极限运动参与者对体育赛事的满意度而言, 复杂性理论原则可以给出更准确的理解. 根据这一观点, 本次研究确定了在从事极限运动赛事的情况下, 建立强大参与者满意度的可能组合. 通过定性比较分析 (QCA), 我们确定了更多可能有助于形成高水平满意度的"食谱". 结果表明, 与赛事相关的属性 (信任, 形象, 态度), 和与极限运动参与者的心理学相关的属性 (感觉寻求, 感知控制), 共同对所有"食谱"作出了贡献. 此外, 如果他们的形象良好, 并且参与者觉得能够控制挑战, 那么即使姿态很低, 也仍然可能会对赛事感到满意.